2019
DOI: 10.1002/iub.2101
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, overexpression, purification, and modeling of a lectin (Rhinocelectin) with antiproliferative activity from Tiger Milk Mushroom, Lignosus rhinocerus

Abstract: A lectin gene from the Tiger Milk Mushroom Lignosus rhinocerus TM02® was successfully cloned and expressed via vector pET28a in Escherichia coli BL21(DE3). The recombinant lectin, Rhinocelectin, with a predicted molecular mass of 22.8 kDa, was overexpressed in water‐soluble form without signal peptide and purified via native affinity chromatography Ni‐NTA agarose. Blast protein analysis indicated the lectin to be homologous to jacalin‐related plant lectin. In its native form, Rhinocelectin exists as a homo‐tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…These biochemicals with pharmacological effects play a preventive and therapeutic role in disease. Polysaccharides are one of the therapeutic compounds of L. rhinocerotis, and numerous studies have shown that PLR is related to antitumor and immunomodulatory effects [26][27][28][29]. Phenolic compounds, as natural antioxidants, was able to scavenge free radicals, and the quantification of total phenolic content and total flavonoid content can be used as indicators to evaluate antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…These biochemicals with pharmacological effects play a preventive and therapeutic role in disease. Polysaccharides are one of the therapeutic compounds of L. rhinocerotis, and numerous studies have shown that PLR is related to antitumor and immunomodulatory effects [26][27][28][29]. Phenolic compounds, as natural antioxidants, was able to scavenge free radicals, and the quantification of total phenolic content and total flavonoid content can be used as indicators to evaluate antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Cordycepin (3-deoxyadenosine) from C. sinensis expressed cytotoxicity on cultured MDA-MB-231 and MCF-7 human breast cancer cells (Choi et al 2011;Wang et al 2016). Under the influence of cordycepin, the cell viability plummeted, cellular proliferation declined, cellular liberation of lactate dehydrogenase increased and reactive oxygen species generation rose, mitochondrial function was disrupted, and nuclear apoptosis took place in human breast cancer cells.…”
Section: Cordyceps Sinensismentioning
confidence: 99%
“…Rhinocelectin, 22.8-kDa recombinant homotetrameric lectin with a single alpha-helix and eleven beta-sheets, displayed IC50 values of 53.11, 36.52, and 142.19 μg/ml, respectively, against MCF-7 and MDA-MB-231 triple-negative human breast cancer cells and 184B5 human nontumorigenic breast cells. Rhinocelectin treatment caused the breast cancer cells to stay in G0/G1 phase of the cell cycle and undergo apoptosis (Cheong et al 2019).…”
Section: Lignosus Rhinocerotismentioning
confidence: 99%